O impacto do turno de trabalho do pai no desempenho acadêmico e no autoconceito de crianças escolares - Cia, Fabiana (Universidade Federal de São Carlos, 2005)
Studies show that the quality of father-child interactions is a factor that has a direct influence on child development, including the formation of the children s self-concept and their academic performance. In addition to the father wanting to be involved, however, he also needs to have time and energy to invest in this relationship. Given the heavy demands associated with paid employment (long hours, night shifts, etc.), we hypothesized that the fathers involvement with their children would be influenced by some of their work conditions. Thus, the aims of this study were: a) identify differences that exist between night and dayshifts, with respect to the fathers work conditions, personal wellbeing and family involvement; b) compare fathers who work in these two shifts with respect to the frequency of their participation in their children s daily and academic activities; c) identify work conditions, personal and family factors that influence the frequency of the fathers involvement with their children; d) compare day and nightshift workers children with respect to the frequency of their communication with their fathers, their self-concept and their academic performance; e) examine the correlations that exist between the fathers work conditions, personal and family factors, and the involvement of the fathers with their children, on the one hand, and their children s self-concept and academic performance, on the other hand. The study participants included 58 children in the fifth and sixth grades and their fathers (36 in dayshift jobs and 22 working nightshifts). The fathers completed a questionnaire, Evaluation of work conditions and of parent-child involvement Father´s version . Their children also evaluated the quality of their relationship with their fathers, completing a questionnaire, Evaluating father-child involvement . The Selfdescription questionnaire 1 and the School Performance Test were used o investigate relations between the type and level of the fathers involvement, with their children s self-concept and academic performance. The results show that work conditions and personal and family factors did not differ as a function of the fathers work shift. However, fathers who worked nightshifts indicated that they had less frequent contact with their children, considering the measures used in this study (fatherchild communication; father involvement in childcare; fathers participation in their children s school, cultural and leisure activities; and time that the fathers spend, engaged in activities with their children. In addition, work conditions (interpersonal work environment, work satisfaction and work performance problems) and personal factors (satisfaction with the availability of time for personal activities, and stress) were correlated with the father s sense of adequacy in his family role performance, which, in turn, was positively correlated with the measures used to evaluate the frequency of father-child involvement. The children s reports of the frequency of communication with their fathers and the children s academic performance did not differ as a function of the shift their fathers worked. However, compared to children whose fathers worked dayshifts, the children whose fathers worked nightshifts had a significantly lower academic self-concept. The measures used to evaluate the frequency of the fathers involvement with their children were positively correlated with their children s selfconcept and academic performance. Thus, the lower levels of academic self-concept among children whose father worked the nightshift can be attributed to the less frequent father-child interactions in this group. These results indicate the importance of the father s involvement for the formation of a child s self-concept and their children s academic performance and point to the need for educational interventions directed at fathers, so that they can learn about the many actions that can improve their performance as fathers.
Keywords: Educação especial; Pai; Autoconceito; Rendimento escolar; Turno de trabalho; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL